(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
This article analyzes the issues of using modern pedagogical technologies to improve the effectiveness of music education. It also highlights the importance of interactive methods, information and communication technologies, and innovative approaches in the educational process. It is argued that the use of modern pedagogical technologies in music education serves to develop students’ creative thinking, musical imagination, and practical skills.